Benefits of the Six Sigma Method (DMAIC) and Implementation Suggestion in the Defense Industry: A Literature Review - Widodo, Andik; Soediantono, Dwi (International Journal of Social and Management Studies, 2022)
The purpose of this article is to explore the benefits of implementing six sigma in various industries and provide recommendations to be applied to the defense industry. The method of writing this article is a literature review, which is a review by collecting, understanding, analyzing and then concluding as many as 30 international journal articles published from 2015 to 2021 regarding the application of the six sigma method in various industrial sectors and the defense industry. The analysis used is 30 journal article content analysis, then coding is carried out on the reviewed journal content, the data that has been collected then looks for similarities and differences and then discussed to draw conclusions. The results of the literature review analysis state that the application of the six sigma method can improve quality, productivity, delivery, cost, morale and occupational safety and health in various industries so that the six sigma method is recommended to be applied in the defense industry.